A report of natural enemies of papaya mealybug, paracoccus marginatus (Hemiptera: Pseudococcidae) in Peninsular Malaysia - Mastoi, M. I.; Azura, N.; Muhamad, R.; Idris, A. B.; Solangi, B. K.; Arfan, A. G.; Bhatti, M. I.; Khoso, F. N. (Publications International, 2016)
Papaya mealybug is notorious pest of papaya & other horticultural crops. Keeping in mind the role of parasitoids and predators in pest management, an exploratory study was conducted on the availability of natural enemies of recently introduced papaya mealybug, Paracoccus marginatus in Selangor and Negri Sembilan states of Peninsular Malaysia. Results revealed the presence of two predators (Cryptolaemus montrouzieri and Apertochrysa sp.), one primary parasitoid (Acerophagus papayae) and three hyperparasitoids (Chartocerus sp., Marietta leopardina and Cheiloneurus sp.). Among all natural enemies recorded, populations of C. montrouzieri and A. papayae were frequently recorded from all sampled locations of the two states. Accordingly, these two species should be exploited for their potential to manage populations of P. marginatus below threshold levels.